Radiation-grafted membranes for polymer electrolyte fuel cells: current trends and future directions - El-Sayed Nasef, Mohamed Mahmoud (American Chemical Society, 2014)
Fuel cell technology is one of the key emerging technologies that is currently attracting tremendous effort with the aim to provide alternative environmentally friendly and efficient power sources. The worldwide move away from conventional fossil fuel combustion power generation technologies is driving much of this important research. The replacement of a liquid electrolyte by PEM in such systems has eliminated the corrosion problems and conferred on the system additional advantages such as simplicity of construction, compactness, and quick self-starting at ambient temperatures. The successful performance of these kinds of fuel cell systems depends critically on the role played by the PEM. The second category involves the formation of acid-base complexes that provide a viable alternative for membranes that can maintain high conductivity at elevated temperatures without suffering from dehydration effects.